Hubungan antara Perhatian Orang Tua terhadap Hasil Belajar Matematika Siswa Kelas IV SDN Tangerang 15 - Amalia Muthia Khansa; Septy Nurfadhillah; Najib Hasan (ALSYS, 2022)
This study aims to determine whether there is a significant relationship between the relationship of parental attention to student learning outcomes in fourth grade mathematics at SDN Tangerang 15 Tangerang City. This study uses a quantitative method of correlation using a survey which was analyzed descriptively. The population subjects in this study were all students of class IV B SDN Tangerang 15, totaling 15 students. The technique of collecting data was using a questionnaire statement instrument consisting of 20 statements and a test instrument for students' mathematics learning outcomes to change fractions in the form of PG consisting of 20 valid and reliable questions. To test the significance of the regression in this study, the value of Thitung 8,663 > Ttable 2,160. As for testing the hypothesis from the results of the correlation test, the correlation coefficient value is 0.923 and the coefficient of determination is 0.852 so that parents' attention has a high contribution of 85.2% to student learning outcomes while the remaining 14.8% is influenced by other factors, it is concluded that there is a significant relationship between parental attention to student learning outcomes in mathematics in grade IV SDN Tangerang 15 Tangerang City. This can be interpreted that the contribution of parental attention to student learning outcomes has a high correlation, the higher the attention given by parents, the higher the learning outcomes obtained by a child.